Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species - Marques, Dayse W.a.; Rafael, José A. (Zootaxa, 2016)
Latheticomyia Wheeler is a small New World genus, with five described species. Here two species from Peru, Latheticomyia peruana sp. nov. and Latheticomyia xantha sp. nov. are described and illustrated. The male of L. longiterebra Hennig is described and illustrated for the first time. Additionally, a key to species is provided.